1995
DOI: 10.1016/s1044-0305(05)80053-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of disulfide linkages and disulfide bond scrambling in recombinant human macrophage colony stimulating factor by fast-atom bombardment mass spectrometry of enzymatic digests

Abstract: Fast-atom bombardment mass spectrometry was used to study disulfide bonding patterns in heat-denatured human recombinant macrophage colony stimulating factor (rhM-CSF). The heat-denaturated protein was studied by analysis of the pattern of peptides in the proteolytic digests. Native rhM-CSF is a homodimer with intramolecular disulfide linkages between Cys7-Cys90, Cys48-CysI39, and Cysl02-Cysl46 and intermolecular linkages between Cys31-Cys31, and the pairs Cys157 and Cys159. Brief heating for 1 min leads to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Digestion was carried out at pH 7.5 at 37°C but was limited to 2 h to minimize possible disulfide bond scrambling (14,15,38). MALDI-MS peptide mapping showed comparable spectra as with reduced MalS, but additional ion signals were observed that could not be addressed as tryptic peptides but as disulfide-bonded dipeptides at m/z 4515, assignable as T2-S-S-T3; at m/z 2544, assignable as dipeptide T7-S-S-T42; and at m/z 2586, assignable as dipeptide T3-S-S-T7, respectively.…”
Section: Migration Of Mals On Sds-page Undermentioning
confidence: 99%
“…Digestion was carried out at pH 7.5 at 37°C but was limited to 2 h to minimize possible disulfide bond scrambling (14,15,38). MALDI-MS peptide mapping showed comparable spectra as with reduced MalS, but additional ion signals were observed that could not be addressed as tryptic peptides but as disulfide-bonded dipeptides at m/z 4515, assignable as T2-S-S-T3; at m/z 2544, assignable as dipeptide T7-S-S-T42; and at m/z 2586, assignable as dipeptide T3-S-S-T7, respectively.…”
Section: Migration Of Mals On Sds-page Undermentioning
confidence: 99%
“…Molecular mass analyses identify the peptides and disulfide-bonded dipeptides by assigning the observed ion signals to the corresponding calculated masses from the amino acid sequence. To confirm whether or not an observed peak in the recorded mass spectrum represents a disulfide-linked dipeptide, a chemical reduction reaction is performed afterward with the sample either in vitro (4,5,7) or on target (8 -11). Subsequent re-analyses of these samples by matrix-assisted laser desorption/ionizationmass spectrometry (MALDI-MS) 1 should show the disappearance of the ion signals from dipeptides that are disulfide-linked and the appearance of signals corresponding to the resulting pairs of reduced peptides.…”
mentioning
confidence: 99%
“…The problem of analysing reduced proteins and their digests is the (possibly uncontrolled) refolding of the protein and the recombination of cysteinyl peptides effecting "disulfide bond scrambling" [114], i.e., the creation of protein or peptide artefacts with non-native disulfide linkages. This obstacle can be circumvented by acidic quenching of the reduction, since reduced thiols are stable at low pH.…”
Section: Determination Of Disulfide Bond Positionsmentioning
confidence: 99%
“…In more recent studies, proteins were reduced under non-denaturing conditions and the reduced cysteines were probed with dithiol specific reagents, that exclusively cross-link spatially (not necessarily sequentially) vicinal thiol groups [114][115][116]. This protein chemical approach enables the spatial differentiation of cysteinyl thiol groups and provides a tool for probing protein folding and its intermediates.…”
Section: Determination Of Disulfide Bond Positionsmentioning
confidence: 99%